ABORDAREA INTEGRALISTĂ A CONŞTIINŢEI ECOLOGICE - USM ADMIN (Moldova State University, 2011)
Ecological Consciousness ensures the knowledge / understanding by a human being of the world and himself in the world which by its complex nature proves a complex approach of towards the training on the coordinates: ecological, physical, social, legal, psychological, spiritual, ethical, aesthetic and educational. Ecological Consciousness is formed not only through the outer world of human knowledge, but also through the knowledge of the intimate universe of the man, manifested in his ethical and moral, esthetic, social and political, legal, cultural and spiritual and educational behavior - the last one synthesizing them all.